Paranoia and Pain Embedded in the Prose of Ismail Kadare - Lumi, Elvira; Shella, Mirela (Richtmann Publishing, 2012)
Kadare's work is a unique combination of paranoia and human suffering under totalitarian oppression. In his writing, wediscover the paradox of civil, psycho-pathological fear of the individual under the state hierarchy and the intellectual pain to 'absurddeath' of everyday life. Paranoia and pain compete with each other as a mental disillusion and illusion of a society in the 'sleep oftotalitarianism’. Kadare makes anatomy of criticism and inserted as a rider battles in the brains of totalitarianism that consisted of thismixture Macbethian, which Surfaces as a crime of power and 'witch hunt' that the writer has to offer with anxiety and tension at the sametime. Danger exists as a psycho-physical violence that causes excessive fear of dictatorship in order to manipulate defense interests ofthe people in power. It is this mental illness that appears as hatred for 'others' and love 'yourself' as a fear of the quick end and the panicof death.